Thesaurus-enhanced Search Moves: An Evaluation of Search Term and Search Result Satisfaction - Shiri, Ali (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper reports on a user-centred evaluation of search process characteristics within a thesaurus-enhanced search environment and the ways in which these characteristics affect users’ judgment of search terms and results. The study has addressed the questions relating to the types of search moves and the relationship between search moves and search terms and results. Cet article présente une évaluation orientée-utilisateur des caractéristiques du processus de recherche à l’intérieur d’un environnement de recherche enrichi d’un thésaurus et les manières dont ces caractéristiques ont un impact sur le jugement des utilisateurs sur les termes de recherche et les résultats. Cette étude examine les problèmes reliés aux types de procédures de recherche et la relation entre ces procédures, les termes de recherche et les résultats.